What are the influencing factors of online learning engagement? A systematic literature review - Hu, Juan; Xiao, Wen (Frontiers in Psychology, 2025)
Since the onset of the COVID-19 pandemic in early 2020, online learning has gained widespread adoption as a learning mode in both K-12 and higher education. Learning engagement serves as a crucial indicator of learning quality and is highly correlated with students’ persistence, satisfaction, and academic performance. Numerous researchers have conducted investigations into the factors that influence online learning engagement. This study employs a systematic literature review methodology to synthesize 55 empirical studies published between January 2020 and July 2023. The research findings reveal the following: (1) Community of Inquiry Theory, Self-determination Theory, Social Cognition Theory, Transaction Distance Theory, and Technology Acceptance Model are the most frequently utilized theories employed by researchers to analyze the influencing factors of online learning engagement. (2) Factors that influence online learning engagement from the learners’ perspective include Motivation, Digital Experience and Literacy, Emotions and Regulatory Strategies, Psychology, Self-Perception, Self-efficacy, and Self-Directed Learning. Additionally, factors from the environment encompass Instrument, Task characteristics, Digital Platforms and Equipment, Physical Environment, Collaboration, and Interaction. (3) Effective strategies to enhance online learning engagement comprise setting clear learning goals for learners, improving their information and social media literacy, strengthening their self-directed learning ability, providing robust instructor support, and creating an optimal learning environment. Through this comprehensive review, researchers interested in this topic will gain a broader understanding, while also obtaining evidence-based insights and valuable recommendations for future research.